Relationship between mutuality and depression in patients with chronic heart failure and caregivers in China: An actor-partner interdependence model analysis - Zhou, Ting; Qu, Jiling; Sun, Huiping; Xue, Mengxin; Liu, Yongbing (Frontiers in Psychology, 2022)
Background: Patients with chronic heart failure and their family caregivers may experience adverse emotional problems, such as depression. Mutuality, which refers to the relationship between caregivers and those they care for, is an important factor affecting depression in the dyads. The purpose of this study was to investigate the relationship between mutuality and depression in patients with CHF and their caregivers in China. Methods: In this cross-sectional study, we used the Mutuality Scale and the Self-Rating Depression Scale to measure mutuality and depression of patients and caregivers. We used SPSS version 26.0 and AMOS version 21.0 to analyze the data. An APIM was established to analyze the actor-partner effects of patient-caregiver mutuality and depression. Results: A total of 250 dyads of patients and caregivers were included in the study. There were statistically significant differences in mutuality and depression between CHF patients and caregivers. The 4 dimensions of patients’ mutuality all have the actor effect on depression. There were 3 partner effects of caregivers’ “pleasurable activities”, “shared values”, and “reciprocity” on depression. Regarding caregiver depression, we only found an actor effect of caregivers’ “shared values” on depression. Conclusion: The relationship between patients and caregivers should be evaluated in the clinical setting, and it is very important to develop intervention measures to improve the adverse emotional problems affecting both patients and their caregivers.